2015
DOI: 10.12952/journal.elementa.000051
|View full text |Cite
|
Sign up to set email alerts
|

From California dreaming to California data: Challenging historic models for landfill CH4 emissions

Abstract: Improved quantifi cation of diverse CH 4 sources at the urban scale is needed to guide local GHG mitigation strategies in the Anthropocene. Herein, we focus on landfi ll CH 4 emissions in California, challenging the current IPCC methodology which focuses on a climate dependency for landfi ll CH 4 generation (methanogen-esis), but does not explicitly consider climate or soil dependencies for emissions. Relying on a comprehensive California landfi ll database, a fi eld-validated process-based model for landfi ll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 71 publications
5
48
1
Order By: Relevance
“…We first evaluate the nonleak periods in 2015 and 2016. In this study (Wong et al, 2016), a larger peak in winter that cannot be attributed to landfill emissions (see section 4.5 in Wong et al, 2016, andK. This agrees with the prior work using independent top-down (tracertracer) flux estimation methods by Wong et al (2016), which showed significant variability in monthly top-down CH 4 emissions estimates.…”
Section: Resultssupporting
confidence: 90%
“…We first evaluate the nonleak periods in 2015 and 2016. In this study (Wong et al, 2016), a larger peak in winter that cannot be attributed to landfill emissions (see section 4.5 in Wong et al, 2016, andK. This agrees with the prior work using independent top-down (tracertracer) flux estimation methods by Wong et al (2016), which showed significant variability in monthly top-down CH 4 emissions estimates.…”
Section: Resultssupporting
confidence: 90%
“…If we assume that the CH 4 average we obtained (67 mol/s) for the city-wide total is representative, the Lamb et al (2016) value for the SSLF represents 46% of the city-wide total. Variability of CH 4 emissions from landfills is partially dependent on the local climate, which can influence the seasonal oxidation of landfill covers (Xu et al, 2014;Spokas et al, 2015). To better understand the variability of the SSLF emissions, we considered several factors known to influence landfill emissions, such as change in barometric pressure over time, air temperature and precipitation (Xu et al, 2014;Spokas et al, 2015).…”
Section: Variability Of Ch 4 Emissionsmentioning
confidence: 99%
“…Variability of CH 4 emissions from landfills is partially dependent on the local climate, which can influence the seasonal oxidation of landfill covers (Xu et al, 2014;Spokas et al, 2015). To better understand the variability of the SSLF emissions, we considered several factors known to influence landfill emissions, such as change in barometric pressure over time, air temperature and precipitation (Xu et al, 2014;Spokas et al, 2015). However, no particular correlations were found between aircraft-determined CH 4 emission rates (the part attributed to the landfill) and average atmospheric temperature recorded at Indianapolis International airport during the experiments (data downloaded from http://www.ncdc.noaa.gov/qclcd/QCLCD, accessed on 10/05/2015), as well as with relative humidity and barometric pressure.…”
Section: Variability Of Ch 4 Emissionsmentioning
confidence: 99%
“…Neither the theoretical generation nor the % recovery efficiency can be routinely validated by field data and, indeed, has been rarely quantified at field scale (Spokas et al, 2006). Recently, as discussed in Spokas et al (2015), 2010 field data for 129 well-managed California landfills indicated a robust linear relationship (r 2 = 0.85) for measured landfill CH 4 recovery compared to measured wastein-place (approx. 125 Nm 3 CH 4 per million Mg landfilled waste).…”
Section: Area-specific Emissions: Spatial Variability and Uncertaintymentioning
confidence: 99%
“…125 Nm 3 CH 4 per million Mg landfilled waste). As the California dataset included open/closed sites, small/large sites, old/new sites in all climatic regions of the state, this simple relationship contradicts the HH-1 first order kinetic equation where biogas generation peaks in the year of disposal with an exponential decline thereafter (See additional discussion in Spokas et al, 2015;Bogner et al, 2016). Moreover, under current regulations, U.S. landfills are required to perform routine quarterly monitoring for CH 4 concentrations near the ground surface followed by remediation and re-testing where elevated concentrations are observed, thus periodically checking for CH 4 leakages.…”
Section: Area-specific Emissions: Spatial Variability and Uncertaintymentioning
confidence: 99%